Cereal size, AMS and charcoal data from phase 1 of the Kashmir Prehistory Project. (April 2022) - Spate, Michael; Yatoo, Mumtaz A.; Shen, Hui; Pokharia, Anil K.; Shah, Mohammad Ajmal; Betts, Alison
Highlights: Presentation of new Neolithic archaeobotanical data and AMS dates from Kashmir Valley. Charcoal identifications indicate wide range of landscape utilisation and possibly include exotic taxa. Cereal measurements indicate reduction in grain size over time, possibly resulting from movement of cultivars into mountain environment. Abstract: Recent archaeobotanical data from preliminary fieldwork during Phase 1 of the Kashmir Prehistory Project has documented the presence of West and East Asian cereals and pulses in contexts dating to ca. 2400 BCE in the Kashmir Valley. Based on these data and the geography of the Kashmir Valley, we have interpreted the valley to be an important node in a network of agro-pastoralist contacts connecting South, Central and East Asia in the 3rd-2nd millennium BCE. Here we present remaining unpublished archaeobotanical materials, AMS dates and charcoal identifications from the first seasons of fieldwork in Kashmir. Preliminary analysis of cereal grain size indicates a morphology comparable to other wheat and barley types in mountainous areas of Asia during prehistory. Identified charcoals may indicate a wider range of resource utilisation than previously understood at Neolithic settlements in the valley.